Mineração no Roteiro da Missão Cruls: ressignificação da fronteira no Planalto Central do Brasil - Adriano Gonçalves da Silva; Rita de Cássia Martins de Souza (Confins)
Mining has been one activity that often led to an intense transformation of the Brazilian territory since the Colonial Period. The Roteiro da Missão Cruls, the subject of research of this paper, consist to form a region of fundamental role for the State’s strategy of unify the National Territory and to establish the frontiers of Brazil, at least, since the Independence in 1822. On the following pages, it defends that the area is a geo-strategic region used by the Brazilian State, even though not in administrative management, in order to guarantee the territorial unit and, by corollary, the unit of its internal market. Nowadays, due to the great changes imposed by the globalization process, this frontier has been given new meanings following a demand of the hegemonic mode of production. Strategic minerals present in the area such as gold, copper, niobium, nickel and zinc, are used on the new technologies developed and highlighted in the global scenario for a fabrication of indispensable materials in modern society. The relation between the State and the transnational corporations are also modified because of the dispute on the control of national and international markets up the new faces of the capital. This work presents the importance of the mining activity at the Roteiro da Missão Cruls for Brazil, a country in which the frontiers are often resignificated. The minerals found in the region, encrusted in the Planalto Central do Brasil, are analyzed here from the strategic point of view for Brazil’s international context, based on data extracted from IBRAM, DNPM, CPRM and MME.